레이저흡수분광 토모그래피법에서의 레이저빔의 최적 배치에 관한 연구 - 김경원(Kyungwon Kim); 윤동익(Dongik Yoon); 최두원(Doowon Choi); 조경래(Gyeongrae Cho); 도덕희(Deoghee Doh) (한국수소 및 신에너지학회 논문집, 2017)
The measurement accuracy of Tunable Diode Laser Absorption Spectroscopy based Tomography (TDLAST) for the temperature and concentration fields are dependant upon the arrangement method of the used laser beams. This paper reports on the optimization of laser beam arrangements using phantom data. It has been verified that the measurement error of the TDLAST decreased with increase of laser beam numbers. Further, it has been confirmed that perpendicular arrangements between the horizontal and the vertical laser beams without additional diagonal laser beams shows the minimum measurement errors.